A quasi-one-dimensional ice mélange flow model based on continuum descriptions of granular materials - J. M. Amundson; A. A. Robel; J. C. Burton; K. Nissanka (The Cryosphere)
Field and remote sensing studies suggest that ice mélange influences glacier–fjord systems by exerting stresses on glacier termini and releasing large amounts of freshwater into fjords. The broader impacts of ice mélange over long timescales are unknown, in part due to a lack of suitable ice mélange flow models. Previous efforts have included modifying existing viscous ice shelf models, despite the fact that ice mélange is fundamentally a granular material, and running computationally expensive discrete element simulations. Here, we draw on laboratory studies of granular materials, which exhibit viscous flow when stresses greatly exceed the yield point, plug flow when the stresses approach the yield point, and exhibit stress transfer via force chains. By implementing the nonlocal granular fluidity rheology into a depth- and width-integrated stress balance equation, we produce a numerical model of ice mélange flow that is consistent with our understanding of well-packed granular materials and that is suitable for long-timescale simulations. For parallel-sided fjords, the model exhibits two possible steady-state solutions. When there is no calving of icebergs or melting of previously calved icebergs, the ice mélange is pushed down-fjord by the advancing glacier terminus, the velocity is constant along the length of the fjord, and the thickness profile is exponential. When calving and melting are included and treated as constants, the ice mélange evolves into another steady state in which its location is fixed relative to the fjord walls, the thickness profile is relatively steep, and the flow is extensional. For the latter case, the model predicts that the steady-state ice mélange buttressing force depends on the surface and basal melt rates through an inverse power-law relationship, decays roughly exponentially with both fjord width and gradient in fjord width, and increases with the iceberg calving flux. The buttressing force appears to increase with calving flux (i.e., glacier thickness) more rapidly than the force required to prevent the capsizing of full-glacier-thickness icebergs, suggesting that glaciers with high calving fluxes may be more strongly influenced by ice mélange than those with small fluxes.